2022
DOI: 10.1002/jcla.24305
|View full text |Cite
|
Sign up to set email alerts
|

The role of platelet parameters for the diagnosis of preeclampsia among pregnant women attending at the University of Gondar Comprehensive Specialized Hospital antenatal care unit, Gondar, Ethiopia

Abstract: Background: Preeclampsia (PE) is a pregnancy-related illness characterized by high blood pressure (BP) and proteinuria after the 20th gestational week (GW). Platelet (PLT) parameter changes are the common hematological abnormalities observed in PE patients. The main aim of this study was to assess the role of PLT parameters for PE diagnosis among pregnant women. Methods:A comparative cross-sectional study was conducted at the University of Gondar Specialized Hospital. A total of 126 pregnant women (63 normoten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 43 publications
2
6
0
Order By: Relevance
“…In our study, the ROC curve analysis showed that the PLT‐I had the largest AUC among the platelet indices, however, the MPV at a cutoff of 11.3 fL, presented better sensitivity, specificity, PPV, and NPV for the prediction of PE. These findings agree with other studies 14,29 …”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…In our study, the ROC curve analysis showed that the PLT‐I had the largest AUC among the platelet indices, however, the MPV at a cutoff of 11.3 fL, presented better sensitivity, specificity, PPV, and NPV for the prediction of PE. These findings agree with other studies 14,29 …”
Section: Discussionsupporting
confidence: 94%
“…These findings agree with other studies. 14,29 The parameter PDW, associated with platelet activation was increased in the PE, and GH groups, which was previously described, 30 although no significant increases in PE patients in comparison to normotensive controls were also reported. 22 The PDW can also be associated with the severity of PE.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Platelet count was significantly lower in a preeclamptic group compared to that in a control group, whereas MPV and PDW were significantly higher in women with preeclampsia [ 48 ]. Platelet count had a significant but negative correlation with the duration of hypertension illness, while MPV showed a positive and significant correlation [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is a marker of PLT size, function, and activation as the number and size of pseudopodia increases during PLT activation [ 20 ]. The increased consumption of PLTs obligated the bone marrow to produce and release young and large PLTs [ 15 , 21 ] leading to an increase in MPV in PE patients [ 22 , 23 ]. There were studies conducted on the association of PLT parameters with PE, however, the findings were controversial.…”
Section: Introductionmentioning
confidence: 99%